Sosialisasi, Edukasi Penerapan Protokol Kesehatan Pada Masa New Normal Di Desa Ruyung Tahun 2021: Sosialisasi, Edukasi Penerapan Protokol Kesehatan Pada Masa New Normal Di Desa Ruyung Tahun 2021 - Saudah Saudah (Yayasan Ahmad Mansyur Nasirah, 2022)
Corona virus as a virus that will cause the common cold to more severe diseases such as Middle East Respiratory Syndrome (MERS-CoV) and Severe Acute Respiratory Syndrome (SARSCoV). When the Covid-19 pandemic occurred, Indonesian people who had various social characteristics, ranging from age group, education level, economic status, were exposed to the internet/mass media, social environment, culture, ethnicity, and others and had different understandings and attitudes. various aspects of the Covid-19 pandemic, not all members of the public comply with health protocols. The habit of washing hands using water alone cannot protect every individual from bacteria and viruses found on their hands. Especially if you don't wash your hands under running water. Moreover, the habit of using and sharing hand washing containers is the same as sharing germs with each other and still allowing germs to stick to hands. This habit must be abandoned and changed to a better one with standard procedures for washing hands with soap. Wearing a mask also protects the lungs from pollution, prevents disease transmission and prevents the face from being exposed to excessive sunlight. While maintaining distance is an action to prevent infectious diseases, by keeping a distance between one person and another can prevent the transmission of covid-19. The purpose of this community service is to provide education to the public about health protocols. The method in implementing this service goes through several stages, namely first, by reviewing the location to be addressed and then conducting discussions with the management. understanding of health protocols after being given education obtained respondents who already understood as many as 68% and respondents who did not understand decreased to 32%, it was concluded that there was an increase in understanding of health protocols in the new normal period. It is hoped that the community will continue to maintain health protocols to break the chain of the spread of COVID-19.